The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.4049/jimmunol.179.2.812
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Trigger Tumor Cell Death by a Nitric Oxide-Dependent Mechanism

Abstract: Dendritic cells (DCs) are well known for their capacity to induce adaptive antitumor immune response through Ag presentation and tumor-specific T cell activation. Recent findings reveal that besides this role, DCs may display additional antitumor effects. In this study, we provide evidence that LPS- or IFN-γ-activated rat bone marrow-derived dendritic cells (BMDCs) display killing properties against tumor cells. These cytotoxic BMDCs exhibit a mature DC phenotype, produce high amounts of IL-12, IL-6, and TNF-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 47 publications
2
51
1
Order By: Relevance
“…This has been described in rodent as well as human systems, and has been attributed to various mechanisms such as TNF, TRAIL, Fas ligand, NO, and perforin/granzyme (12)(13)(14)(15). Although the physiological relevance of DC cytotoxicity remains uncertain, there are clear potential applications for cultured DC with the ability to kill tumor targets, particularly if this killing is specific to tumor, as opposed to normal cell, targets.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
See 1 more Smart Citation
“…This has been described in rodent as well as human systems, and has been attributed to various mechanisms such as TNF, TRAIL, Fas ligand, NO, and perforin/granzyme (12)(13)(14)(15). Although the physiological relevance of DC cytotoxicity remains uncertain, there are clear potential applications for cultured DC with the ability to kill tumor targets, particularly if this killing is specific to tumor, as opposed to normal cell, targets.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…Surprisingly, it appeared that neither the CD4 nor CD8 T cells were responsible for the majority of the innate killing observed, as a significant cytotoxic component was always found in those cells remaining after CD4 or CD8 isolation. Because the OK-DC themselves always remained in the cytotoxic fraction, and direct killing by DC has been previously reported (12)(13)(14)(15), this led us to question whether the OK-DC were directly responsible for tumor cell target death. In initial experiments, we positively selected CD86-expressing cells from the T/OK-DC cocultures (as a marker expressed by DC but not T cells), and found that indeed significant cytotoxicity resided in this CD86 ϩ fraction (data not shown).…”
Section: Ok432 Enhances DC Migrationmentioning
confidence: 99%
“…While the demonstration of direct DCmediated killing of tumor cells in vivo is a technically daunting agenda, intra-tumoral injection of DC or treatment of tumors with DC-activating factors has been shown to correlate with reduced tumor growth and even regression. 9,10,12,21,35,46 Clearly such anti-tumor activity could prove the result of KDC activity, but it could equally well involve DC-induced tumoristatic/antiangiogenic properties 34,43 and/or the ability of lesion associated DC to activate effector NK and T cells that could themselves mediate tumor cell death. 32 Studies of DCmediated tumor apoptosis in T/NK-deficient hosts could prove instrumental in visualizing direct killing of tumor cells in situ by DC; although it is likely that tumor regression would not be observed under these conditions, since both T and NK would likely be required for complete tumor eradication.…”
Section: Dc-mediated Tumoricidal Activity In Vivomentioning
confidence: 99%
“…12 As previously mentioned, NO appears to represent yet another lytic agent, or (at least) a sensitizer of tumor cells to cytotoxicity mediated by both rodent KDC. 9,10,11,13 Human DC generated in vitro from monocyte (mono-DC) precursors have also been reported to kill various tumor cell lines in the absence of overt exogenous stimuli (Table 3). 19,22,33,34,36 The specific mechanism(s) by which these DC promote the demise of tumor cells remains highly controversial, with numerous examples of directly conflicting reports.…”
Section: Cultured Kdc Generated From Bone Marrow Progenitor Cells or mentioning
confidence: 99%
“…Rat cytotoxic DCs express NK receptor protein 1 (NKR-P) (11) and the human and mouse NK group 2 member D (NKG2D) ortholog NKR-P2 (12,13). It was recently reported that bone marrow DC (BMDC) cytotoxic activity requires a direct contact with target tumor cells and depends on NO production (14). NKR-P2/NKG2D is a disulfide-linked type II C-type lectin-like receptor expressed also on NK cells, CD4 ϩ , CD8 ϩ ␣␤, ␥␦ ϩ T cells (15), rat CD4 ϩ /CD8 ϩ monocytes and macrophages (16), mouse IFN-producing killer DCs (17,18), and human myeloblastic KG1a cells (19).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%